Laterality in foraging phalaropes promotes phenotypically assorted groups. (21st October 2020) - Gutiérrez, Jorge S; Soriano-Redondo, Andrea
Abstract: Asymmetry of the brain and behavior (lateralization) is widespread in the animal kingdom and could be particularly advantageous for gregarious organisms. Here, we investigate the possibility that lateralized behaviors affect the structure of foraging flocks. Phalaropes (Scolopacidae: Phalaropus ) are highly aquatic shorebirds and the only vertebrates that spin on the water to feed, often in large flocks. There is anecdotal evidence that individuals spin in a single direction and that those spinning counter the majority are usually found at the periphery of a flock. Although such phenotypic segregation may reduce interference among socially foraging birds, its extent and underlying mechanism remain unexplored. Using over 900 spinning bouts from freely available video repositories, we find support for individual, but not population, lateralization of spinning in the three phalarope species. Although spinning direction was not determined by the position occupied within a flock (periphery vs. core), nearest neighbors were more likely to spin in the same direction; moreover, they were three times less likely to interfere with each other when aligning spinning direction. Our results indicate that a simple rule (keep foraging with similarly lateralized individuals) can generate self-organized interactions among flockmates, resulting in groups phenotypically assorted. Abstract : In animals, asymmetry of the brain and behavior is the rule rather than the exception. Using videos from online video repositories, we confirm that phalaropes are "handed" during feeding: Birds spin both clockwise and counterclockwise, but each individual almost always spins in one direction. We show that phalaropes tend to associate with near neighbors that spin in the same direction, thus reducing conflicts among flockmates.